Barriers and opportunities related to extracorporeal cardiopulmonary resuscitation for out-of-hospital cardiac arrest in Canada: A report from the first meeting of the Canadian ECPR Research Working Group. Issue 4 (7th May 2018) - Brooks, Steven C.; Shemie, Sam D.; Torrance, Sylvia; Hornby, Laura; Gillrie, Clay; Grunau, Brian; Nagpal, A. Dave; Baker, Andrew; Christenson, Jim; Gill, John; Morrison, Laurie
Abstract : For a French translation of the executive summary, please see the Supplementary Material at DOI:10.1017/cem.2017.429 EXECUTIVE SUMMARY: Extracorporeal cardiopulmonary resuscitation (ECPR) is an emerging therapy for patients with cardiac arrest refractory to conventional resuscitation. ECPR entails the use of extracorporeal membrane oxygenation (ECMO) to sustain perfusion in patients with cardiac arrest. Best available evidence from around the world is of low quality, but observational studies have suggested that ECPR is associated with increased survival in subgroups of out-of-hospital cardiac arrest (OHCA) patients and provides organ donation opportunities in non-survivors. Organized by Canadian Blood Services in collaboration with the Canadian Resuscitation Outcomes Consortium, we assembled an interdisciplinary group of clinicians and researchers from across Canada, with support from international experts, to discuss opportunities and barriers related to the use of ECPR for OHCA in the Canadian context. Representatives included those with expertise in prehospital medicine, emergency medicine, resuscitation, cardiac surgery, ECMO, neurology, neurointensive care, critical care, organ donation, transplantation, health policy, health economics, and bioethics.